L-Lysine Production By Mutant Strains Of Corynebacterium Glutamicum Using Molasses - Budiatman Satiawihardja; Erliza Noor; Ahmad Haryo Oktamto (Jurnal Teknologi dan Industri Pangan, 2000)
The objective of this study was to obtain fermentation process for producing l-lysine using two mutans of Corynebacterium glutamicum. The process used a low cost natural raw material molasses as a carbon source which underwent a special treatment before its application for fermentation medium. Strain Corynebacterium glutamicum ATCC 21543 produced higher L-lysine as compared to Corynebacterium glutamicum ATCC 21513. ATCC strain 21543 produced using a 10.98 g/l L-lysine modified basal B medium containing molasses which was equivalent to 20 % of original molasses in terms of its sugar content.